APPROACHES TO DESIGNING THE MASTER’S PROGRAM “PHYSICS AND MATHEMATICS EDUCATION” - S. E. Starostina; Y. S. Tokareva (Высшее образование в России)
The article presents a spectrum of approaches to designing the master’s program «Physics and Mathematics Education» in the context of the introduction of professional standards, including the following: an analysis of the requirements of the regional labor market; consideration of different levels of training and motivation of different target groups; methodological bases for determining the structure of competencies; the modular design of educational program; determination of module content and technological content; an analysis of professional standards and their relationship with the Federal state educational standard of higher education; organizational and methodical approaches to assessment of results through different types of practices; introduction of the final interdisciplinary examination in the subject modules. The paper gives recommendations on making the changes in the organization of the educational process at university: at the level of a teacher, at the level of educational program realization and at the level of university.